2005
DOI: 10.1038/sj.npp.1300961
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Decreased Plasma NO Metabolites and Platelet NO Synthase Activity by Paroxetine in Depressed Patients

Abstract: Although major depression (MD) and cardiovascular disease (CVD) have been conclusively linked in the literature, the mechanism associating MD and CVD is yet undetermined. The purpose of this paper is to further investigate a potential mechanism involving nitric oxide (NO) and to examine the effect of the selective serotonin reuptake inhibitor paroxetine on NO production by both platelets and the endothelium. In total, 17 subjects with MD and 12 healthy controls (HCs) with no known history of cardiovascular ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 53 publications
3
56
1
Order By: Relevance
“…In BP-I patients, plasma levels of NO were found to be higher [6,7] . Four studies with the SSRI paroxetine presented with conflicting results, in that Finkel et al [12] and Goodnick and Goldstein [41] reported decreased serum nitrite and nitrate levels following paroxetine treatment, whereas Lara et al [42] and Chrapko et al [27] found the reverse.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In BP-I patients, plasma levels of NO were found to be higher [6,7] . Four studies with the SSRI paroxetine presented with conflicting results, in that Finkel et al [12] and Goodnick and Goldstein [41] reported decreased serum nitrite and nitrate levels following paroxetine treatment, whereas Lara et al [42] and Chrapko et al [27] found the reverse.…”
Section: Discussionmentioning
confidence: 92%
“…Since most of the patients from the bipolar groups were treated with psychotropics and mood stabilizers other than lithium, and these compounds are known to modify the here studied biochemical parameters [23][24][25][26][27] , symptomatic bipolar patients on monotherapy with lithium were compared to the euthymic monolithium bipolar patient control group. Analyses of the biochemical parameters in the monolithium symptomatic subgroup revealed similar results with respect to decreased neopterin levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, although an initial study with paroxetine suggested that this drug may cause reduction in NO bioavailability, 38 subsequent studies have shown that the selective serotonin reuptake inhibitors most commonly used in this study improve vascular endothelial function. 39 -42 Thus, both paroxetine 39,40 and citalopram 42 increase plasma NO metabolic end products in control participants and in patients with depression. In addition, sertraline improves brachial artery flow-mediated dilation in depressed patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Or, platelet NO production may precede clinical changes in vascular function, such as FMD 44 ; longer SSRI treatment duration may have shown more significant vascular effects. The literature regarding SSRI effects on platelet NO production is highly mixed, with some studies showing SSRI treatment leading to decreased (citalopram 45 ), no effect (paroxetine 46 ), or increased (paroxetine 18,47 ) plasma NO levels with no effect on nitric oxide synthase (NOS) activity observed in some studies. 18 The connection between NO function and depression is complex, particularly in that plasma levels of NO do not specifically reflect platelet or endothelial NO production.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Platelet nitric oxide (NO) production, which may influence platelet aggregation, [13][14][15] is dysregulated among cardiovascular patients 16,17 and depressed individuals. 18 The impact of depression on cardiovascular health may be buffered by antidepressant medications. Several but not all reuptake inhibitors (SSRIs) on cardiovascular health, 20,21 including improved FMD 22 and reduced platelet activation or aggregation.…”
Section: Introductionmentioning
confidence: 99%